Does Hypertension Knowledge Influence Levels of Physical Activity in Hypertensive Patients From a Southern Brazilian Community? - Dos Santos R.Z.* (2021)
© 2021, Sociedade Brasileira de Cardiologia. All rights reserved.Background: Increased level of physical activity (PA) and health education are known as non-pharmacological treatments of hypertension (HP). There is a lack of studies investigating the influence of HP knowledge on the level of PA among hypertensive patients. Objective: To examine the influence of patient’s knowledge about HP on PA level and the relationship between these variables. Methods: A cross-sectional study was conducted in in a primary care center located in a city in the southern Brazil. A total of 199 hypertensive patients (median 61.2 [13] years; body mass index (BMI) 21.9 (7.5) kg/m2; 72.4% women) were included. The level of PA was assessed by measuring the number of steps taken daily. The knowledge about HP was assessed by a standardized questionnaire (HIPER-Q). The Kruskall-Wallis test was used to compare age, BMI and PA level between HP knowledge categories, and the Spearman test was used to assess correlations (<0.05). Results: The median score of knowledge about HP for patients categorized as insufficient (n=6, 3%), poor (n=24; 12.1%), acceptable (n=101; 50.8%) and good (n=68; 34.2%) was 11.0 (8.0), 20.0 (4.0), 26.0 (5.0) and 38.0 (2.0), respectively. No patient has achieved an “excellent” level of knowledge. There was no significant difference in PA level (p=0.341), BMI (p=0.510) or age (p=0.073) between these categories. Age was negatively correlated with knowledge about HP (p<0.05 and rho=0.02). Conclusions: Patient’s knowledge about HP did not influence the level of PA in hypertensive patients. Age, number of steps per day and BMI were not significantly different between the categories of knowledge. Public policies and organizational strategy should be addressed to improve health education and avoid sedentary behavior in this population.